Research and Publication from Developing Countries - Sharma, Mohan R (Journal of Institute of Medicine Nepal, 2020)
In 2002, Richard Smith wrote an editorial, “publishing research from developing countries” in the Journal “Statistics in Medicine” highlighting the importance of research and publication from the developing countries (DCs).1 In that article, he mentioned the disparity in research and publication between the developed and developing countries. Almost two decades on, the problem still largely remains the same. It is estimated that more than 80% of the world’s population lives in more than 100 developing countries.2 In terms of disease burden, the prevalence and mortality from diseases in the low and middle-income countries are disproportionately high compared to developed countries.3 Although there is a high burden of disease, we base our treatment inferring results from research and publication from the developed countries which may not be fully generalizable due to geographical cultural, racial, and economic factors. This is where the problem lies.